DIFFERENCE IN PLATELET COUNT BETWEEN PLATELET APHERESIS AND PLATELET-RICH PLASMA (TC PRP) AT Dr. MOHAMMAD HOESIN CENTRAL GENERAL HOSPITAL PALEMBANG - sri hartini harianja; Sinta Damiyanti; Refai Refai; Yusneli Yusneli; Hamril Dan (Journal of Medical Laboratory and Science, 2025)
Background: Platelet transfusion is an essential medical intervention for patients with thrombocytopenia or abnormalities in hemostasis. Therefore, understanding the quality of platelet components used for transfusion is crucial, including evaluating the platelet count in each unit. According to data from the Blood Transfusion Unit (UTDRS) at Dr. Mohammad Hoesin General Hospital Palembang in 2024, out of a total platelet requirement of 2,904 units, 13,264 units of TC-PRP and 1,540 units of Platelet Apheresis were transfused. Objective: To determine the differences in platelet counts between Platelet Apheresis and Platelet Rich Plasma (TC-PRP) units at Dr. Mohammad Hoesin General Hospital Palembang. Methods: This study was a laboratory-based observational analytic study with a comparative approach. The samples consisted of 20 TC-PRP units and 20 Platelet Apheresis units, selected through purposive sampling. Data were analyzed using the Independent Sample T-Test. Results: The statistical analysis showed a p-value of 0.000 (p < 0.05), indicating a significant difference in platelet counts between Platelet Apheresis and TC-PRP units. Conclusion: The study concluded that the quality of platelet components, based on platelet count, is higher in Platelet Apheresis compared to TC-PRP. Recommendation: Clinicians may prefer platelet apheresis in therapy to achieve more optimal benefits, especially when adequate doses of TC-PRP are difficult to obtain.